An anisotropic damage model based on dislocation-mediated nucleation of cracks under high-rate compression. (April 2020) - Daphalapurkar, Nitin P.; Luscher, Darby J.; Versino, Daniele; Margolin, Len; Hunter, Abigail
Abstract: We developed a thermodynamically-consistent, rate-dependent micromechanics model for brittle damage nucleated by dislocation plasticity applicable for large deformations. Dislocation substructure evolution was used to inform a nucleation criterion for a microcrack. Under global compression, the sliding of a microcrack induces formation of wing cracks. Effective stress drives dynamic growth of these cracks under a 3D stress state, resulting in an anisotropic material stiffness. The model was further advanced to predict grain size dependence of a polycrystalline solid. Internal variables were constrained based on the laws of thermodynamics. Material constants were calibrated for polycrystalline beryllium to demonstrate the applicability of the model to simulate dynamic failure under compression. We demonstrate the versatility of the model to capture brittle to ductile transition governed by temperature and strain rate. The predictive capability of the model to simulate failure stress and failure strain is compared with dynamic and quasistatic data on beryllium.